The Role of Demixing and Crystallization Kinetics on the Stability of Non‐Fullerene Organic Solar Cells. Issue 49 (5th November 2020) - Hu, Huawei; Ghasemi, Masoud; Peng, Zhengxing; Zhang, Jianquan; Rech, Jeromy James; You, Wei; Yan, He; Ade, Harald
Abstract: With power conversion efficiency now over 17%, a long operational lifetime is essential for the successful application of organic solar cells. However, most non‐fullerene acceptors can crystallize and destroy devices, yet the fundamental underlying thermodynamic and kinetic aspects of acceptor crystallization have received limited attention. Here, room‐temperature (RT) diffusion coefficients of 3.4 × 10 −23 and 2.0 × 10 −22 are measured for ITIC‐2Cl and ITIC‐2F, two state‐of‐the‐art non‐fullerene acceptors. The low coefficients are enough to provide for kinetic stabilization of the morphology against demixing at RT. Additionally profound differences in crystallization characteristics are discovered between ITIC‐2F and ITIC‐2Cl. The differences as observed by secondary‐ion mass spectrometry, differential scanning calorimetry (DSC), grazing‐incidence wide‐angle X‐ray scattering, and microscopy can be related directly to device degradation and are attributed to the significantly different nucleation and growth rates, with a difference in the growth rate of a factor of 12 at RT. ITIC‐4F and ITIC‐4Cl exhibit similar characteristics. The results reveal the importance of diffusion coefficients and melting enthalpies in controlling the growth rates, and that differences in halogenation can drastically change crystallization kinetics and device stability. It is furthermore delineated how low nucleation density and large growth rates can be inferred from DSC and microscopy experiments which could be used to guide molecular design for stability. Abstract : Through investigation of the underlying thermodynamic and kinetic aspects of non‐fullerene acceptor crystallization, the importance of diffusion coefficients and melting enthalpies in controlling the crystal growth rates is demonstrated, and it is revealed and that differences in halogenation can drastically change crystallization kinetics and device stability.